Pengembangan E-Comic “Bimanah” (Belajar Ingat Kisah Muhammad Membangun Kota Madinah) sebagai Media Pembelajaran untuk Kelas 4 SD - Agustin, Lisna; Nabila, Tsania Qisma; Rahmatunisa, Anggun Mutiara; Aeni, Ani Nur (Universitas Islam Sultan Agung, 2025)
Abstract This study aims to develop and analyze the effectiveness of the voice-enabled e-comic